Features of violation of maturation of the chorionic tree of the placenta at immaturity of the placental bed of the uterus on the background of iron deficiency anemia in pregnant women in terms of chronic insufficiency of manure - Olena Tiulienieva; Igor Davydenko; Viallanta Tiulienieva; Olena Marchuk; Tetiana Shelest; Oleksandr Volkov (Kazimierz Wielki University, 2021)
The authors of the article investigated the quantitative parameters of the placental chorion tree during physiological pregnancy and gestation against the background of iron deficiency anemia. It has been established that iron deficiency anemia in pregnant women inhibits the development of the placental chorionic tree, which is explained by the formation of chorionic villi (through trophoblastic and free processes) and violation of the transition of terminal villi to terminal "specialized" villi. The diagnosis of chronic placental insufficiency during pregnancy on the background of iron deficiency anemia can be verified morphologically based on quantitative indicators of assessment of the structure of the placental chorionic tree - the percentage of terminal villi should be higher than 43% and the percentage of terminal "specialized" villi lower than 15%.